Association between PFAS exposure and attention processing in adolescent boys: a pilot study - Newman, Sharlene D.; Xiong, Yanyu (Frontiers in Cognition, 2025)
Perfluorinated alkylated substances (PFAS) are a group of chemicals that have been used in industries and products for decades. Little is known about the neurological effects of PFAS in humans, particularly during adolescence, which is a critical period for brain development, making exposure to environmental toxins during this period even more likely to lead to cognitive deficits. We recruited adolescent boys to participate in this pilot study. We performed community data collection of (1) blood sample to measure blood-level PFAS, (2) parental assessments of behavior, and (3) electroencephalography (EEG) data during the performance of an attention task. Our findings demonstrated the feasibility of collecting community data, including EEG data. The data collected revealed an association between PFAS levels and EEG measures of attention, specifically P2 and N2, and parental assessment of attention. Although this is a pilot study, it indicates the feasibility of conducting more comprehensive studies to examine the neurocognitive effects of PFAS exposure.